Teacher Discomfort: The Inclusion of a 5-Year-Old Girl with Microcephaly in the Preschool Classroom - Sánchez-Domínguez, Juan Pablo (2023)
In the Mexican educational system, the Ley General para la Inclusión de las Personas con Discapacidad [LGIPD] establishes the integration of students with disabilities into the regular education classroom without distinction. This requirement has generated in the teaching staff an increase of ethical, personal, and professional demands that in the end can cause discomfort, that is, provoke permanently negative effects in the professors that besides altering their physical and psychological state, deteriorate their performance. The objective of the research was to characterize the factors associated with teacher discomfort in a preschool educator during her work with a child diagnosed with microcephaly. The study was qualitative, cross-sectional, and descriptive given the case study modality. Moreover, the participating teacher was observed in the regular classroom and the information was recorded in a field diary followed by a semi-structured interview. Regarding the elaboration of the data collection instruments and the subsequent interpretation of the results, units of analysis were elaborated within the framework of the theoretical formulations of Esteve (2003) and Cordié (2007). The results show that the working conditions faced by the professor to perform her inclusive work demand a greater physical and psychological effort, which, together with the lack of material resources, teaching assistants, and inclusion training, place her in situations of constant stress and difficulty in assuming the new roles required by the reality she faces in the classroom. In this context, these results offer for further studies the characterization of those discomforts teachers face in response to the provisions of the LGIPD of the Mexican Educational System and for which they are not professionally or personally trained. As a recommendation, it is urgent to review the implementation mechanisms of the LGIPD, mainly in basic education, and to train regular education teachers in inclusion issues and in the adequate management of their emotions.